2015
DOI: 10.1089/jmf.2014.3205
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Major Compounds fromIxeris dentata,Ixeris dentataVar.albiflora,andIxeris sonchifoliaand Their Comparative Anti-Inflammatory Activity in Lipopolysaccharide-Stimulated RAW 264.7 Cells

Abstract: The aim of the present study was to evaluate the comparative anti-inflammatory activities of Ixeris dentata (ID), Ixeris dentata var. albiflora (IDA), and Ixeris sonchifolia (IS) and to identify the main compounds present in extracts. The anti-inflammatory activity was evaluated through lipopolysaccharide (LPS)-induced nitric oxide (NO) production in RAW 264.7 murine macrophages. Five main compounds consisting of chlorogenic acid, caffeic acid, luteolin 7-O-glucoside, luteolin 7-O-glucuronide, and luteolin wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…According to recent research, ID has been proved to have a hypocholesterolaemic effect and an antioxidant activity, as well as ID is known to have aliphatics, triterpenoids and sesquiterpene glycosides in its composition [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to recent research, ID has been proved to have a hypocholesterolaemic effect and an antioxidant activity, as well as ID is known to have aliphatics, triterpenoids and sesquiterpene glycosides in its composition [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…The methanol extract was most effective in the anticancer activity, inhibiting the growth of MG-63 cells by more than ninety percent [8]. Also, the effect of ID on the cardiovascular system in hyperlipidemic rats was examined [8] and also caused prevention of neurodegenerative diseases [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern pharmalogical experiment showed that Kudiezi has many biological activities such as anti-oxidant, antiinflammation, anti-tumor and regulate the immune functions [10]. In celluar in vitro experiment, Karki et al reported that the component of ISH have a potent antiinflammatory activity in lipopolysaccharide-stimulated RAW 264.7 cells [11]. The study of Yang et al showed that ISH have a strong anti-oxidant activity in vitro [12].…”
Section: Introductionmentioning
confidence: 99%
“…The low molecular weight components of Flos Chrysanthemi show great diversity, including flavonoids, sesquiterpenes, triterpenes and unsaturated fatty acids, and some of these compounds contribute to the beneficial functions of Flos Chrysanthemi (Avula et al ., ; Michiko et al , ; Ukiya et al ., . Extensive phytochemical and pharmacological investigation of Flos Chrysanthemi revealed that its major bioactive compounds are flavonoids such as luteolin‐7‐ O ‐glucoside, luteolin, apigenin‐7‐ O ‐glucoside, diosmetin‐7‐ O ‐glucoside, quercetin and acacetin (Aslan & Adem, ; Farag et al ., ; Karki et al ., .…”
Section: Introductionmentioning
confidence: 99%